Treatment of palm oil mill effluent by using 2-stage photo ferrioxalate/TᵢO₂/ozone system - Mohd Fadzil, Nor Aqilah (2013)
The feasibility of advanced oxidation processes (AOPs) named photo Ferrioxalate/TiO2/Ozone system in degrading Palm Oil Mill Secondary Effluent (POMSE) was investigated. The investigation was divided into two major parts; first was the degradation of POMSE by using single (photo Fenton, Ferrioxalate, TiO2 and Ozone) and combined system of AOPs (photo Ferrioxalate/TiO2 and photo Ferrioxalate/TiO2/Ozone) and second was the degradation of POMSE by two stages treatment system. As expected combined processes showed better performance than single systems with the COD removal recorded for photo/Ferrioxalate, photo TiO2 and photo Ferrioxalate/TiO2 were 49 %, 57 % and 65 %, respectively. In addition, two stages treatment system of photo Ferrioxalate/TiO2/Ozone system (photo Ferrioxalate/TiO2 for the first two hours followed by ozonation for another two hours) shows total removal of color and COD. Moreover, more than 85 % removal was recorded for the TOC. On the other hand, single stage treatment process gave only 54 %, 69 % and 61 % removal of COD, TOC and color, respectively. Besides, the effect of H2O2 concentration, TiO2 loading and pH were also studied to determine optimum condition for the removal. The reaction mechanism was illustrated to explained the chemical process occur in all system. First order kinetic model was applied to explain the relationship between initial POMSE concentration and its initial degradation rate. The optimization of single stage treatment process was conducted by using Response Surface Methodology (RSM) and it gave 20 % increment in four hours reaction time with optimum parameters as follow: [H2O2:Fe3+] = 5.5 :1.0; [oxalate: Fe3+] = 5.5 : 1.0 and TiO2 = 225 mg. The optimization was verified by using analysis of variance (ANOVA). Methyl Orange (MO) had been used as colored organic pollutant to observe the feasibility of photo Ferrioxalate/TiO2/Ozone system in treating simple colored wastewater. The results gave total decolorization for 20, 100 and 200 ppm of MO. Meanwhile, almost 90 % decolorization recorded at 500 ppm.